Ethnic differences in peak expiratory flow rate in Birmingham factory workers. Issue 696 (October 1983) - Jackson, S. H.; Beevers, D. G.; Cruickshank, J. K.; Bannan, L. T.
Abstract : Among 698 Birmingham factory workers, Asian men (n = 75) tended to have lower peak expiratory flow rates (PEFR) than black (n = 156) or white (n = 138) men when age, height and smoking habits were accounted for. This trend reached statistical significance in Asian females (n = 20), despite a small sample size. There were no significant differences in PEFR between blacks and whites of either sex.